Reiteration of the elimination status of measles in the southeast of Iran, 2015 - Shahrokh Izadi; Masoome Arabsalmani; Mahdi Mohammadi; Seyed Mehdi Tabatabaei; Ali-Akbar Haghdoost (Taylor & Francis Group, 2018)
During 2015, the number of measles cases reported from Iran increased about three times the previous year; and Sistan-va-Baluchestan Province, located in the southeast of Iran, was the hottest point at the center of the dilemma. The main objective of the present study was to evaluate the situation of the population with regard to the elimination goals. The files of all measles cases were reviewed and categorized again based on surveillance system definitions; and the effective reproduction numbers, attack rates, and epidemic curves were calculated and graphed. In total, 152 laboratory-confirmed cases occurred in 2015 in the study population. The highest attack rate belonged to infants being in their first year of life and the lowest to the age groups 16 to 40. The estimated 'Effective Reproduction Number' for the eight districts ranged from 0.70 to 0.93; and considering the subsidence of all outbreaks by themselves, it might be speculated that elimination state is still in effect and accountable. Considering the large number of the susceptible islands among the sea of herd immune population, implicated by the large number of outbreaks, implementation of a supplementary immunization intervention is highly recommended.